Ritual Compadrazgo as an instrument of Interethnic and Social Adaptation among the Rarámuri in Northwestern Mexico and its Possible Correlations to Local Political Events - Halbich, Marek (Lidé města, 2010)
This paper pursues, on the basis of some field-works among the Rarámuri Indians and the mestizos in northwestern Mexico, namely in the ejido Munerachi and the small Mexican towns Batopilas and Creel, three principal aims: first, it generally outlines the concept of the Mexican ejido; second, it focuses on the application of the theoretical concept ritual (fictive) compadrazgo of the North-American anthropologists Eric Wolf and Sidney Mintz in Lower and Upper Tarahumara in the Indian and the mestizo communities; and, third, it tries to find some possible correlations of the ritual compadrazgo to local political events.